Nighttime Graffiti in the Roman Republic: Populism and the Anti-State - Allen, Joel (Huarte de San Juan. Geografía e Historia, 2024)
This paper contends that populist graffiti in the Roman Republic, including famous examples from the aftermath of Gaius Gracchus’s death and the last weeks of Julius Caesar’s life, were at times intentionally produced at night, not just for the security and anonymity of darkness, but also in order to generate maximum impact, with a daybreak surprise that breached the notional barriers between the populist night and the aristocratic day. Various sources indicate that the formal institutions of the res publica, as dominated by the elite, were largely diurnal in nature, such that the state was effectively suspended at every sunset, and the night became the province of the marginalized. Graffiti from this context, when newly revealed at dawn, thus constituted a missive from an anti-state to the «legitimate» one – a kind of technology of illumination that facilitated popular engagement with political debates from which the people were otherwise procedurally excluded.
Keywords: graffiti; Rome; night; populism; subversion